Germany After the 2013 Elections: Breaking the Mould of Post-Unification Politics? - D'Ottavio, Gabriele (Ashgate Publishing Ltd, 2015)
The German election of 2013 has important ramifications for the whole of Europe. Germany After the 2013 Elections: Breaking the Mould of Post-Unification Politics? provides a comprehensive analysis of this election and its wider implications for post-unification German politics. International specialists on German and EU politics examine the domestic and international context of the election and reflect on its possible consequences. In the first part of the volume, a number of contributors analyse the policy environment in which the election took place while the second part deals with voters
Description based upon print version of record
Keywords: Electronic books